2022
DOI: 10.1088/1742-6596/2325/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of stochastic arithmetic computing and stochastic activation function

Abstract: Stochastic Number Generators (SNG) plays a significant role in designing a stochastic computing system. SNGs make the stochastic system comfortable for computing in the stochastic domain. The challenges in developing the stochastic computing system are correlation and hardware area occupancy. By considering these phenomena, we have considered Linear Feedback Shift Register (LFSR) based SNG and S-box based SNG in this work. Our contributions to this paper are stochastic computation for activation functions usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…An approach for binarized neural networks was developed for the Modified National Institute of Standards and Technology database(MNIST) and Canadian Institute For Advanced Research(CIFAR) data focusing on performance of the convolutional binarized network. This has been extended for ASIC implementations [29][30][31][32]. The authors have suggested the importance of a CNN accelerator and the use of Python as an Algorithmic High-Level Language, for the realization and the implementation and FPGA based accelerators for CNNs.…”
Section: Related Work On Stochastic Computing Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach for binarized neural networks was developed for the Modified National Institute of Standards and Technology database(MNIST) and Canadian Institute For Advanced Research(CIFAR) data focusing on performance of the convolutional binarized network. This has been extended for ASIC implementations [29][30][31][32]. The authors have suggested the importance of a CNN accelerator and the use of Python as an Algorithmic High-Level Language, for the realization and the implementation and FPGA based accelerators for CNNs.…”
Section: Related Work On Stochastic Computing Elementsmentioning
confidence: 99%
“…The main focus of our research work is to build an efficient SC system focusing on accuracy improvement at all levels till the development of the CNN system. As a first step towards the same an S-Box-based the SNG methodology, (where-in the S-Box [34,35] in cryptographic algorithm) is used as the stochastic bit stream generator for building up the SC components. The developed components will be used for the development of CNN layers.…”
Section: Related Work On Stochastic Computing Elementsmentioning
confidence: 99%